Shawqi's Friends, Opponents and Contemporaries - Al-Rifai, Nada Yousuf (Advances in Social Sciences Research Journal, 2024)
This research sheds light on Shawqi's friends, acquaintances and opponents. As the Islamic tradition says, a man follows the religion of his friend, so look at whom he likes. In contemporary history, friendships between writers decreased and feelings of envy, hatred and competition for glory, fame and influence prevailed among them. This is what we see through the tense relations between great Egyptian writers, such as Taha Hussein, Al-Aqqad and Mustafa Al-Sadiq Al-Rafi’i in the 1930s and 1940s. The conflicts between Arab poets were intense, even if they belonged to the same movement. In contrast, there were writers who had beautiful friendships, lofty goals and literary ambitions, as were the friendships of Ahmed Shawqi. Shawqi had few friends yet many acquaintances. He selected his friends in the same way as a skilled jeweler would select exquisite gems to complete his creation and expensive handicraft masterpiece. He did not feel comfortable except in the company of a limited number of lighthearted people with sublime taste. Among those close to him were Mohammed Al-Babily, Dr Mahjoub Thabet and Sheikh Tamarah, who was imam of the Egyptian embassy in Washington at the time, as well as Hussein Shirin, Mohamed Jaziri and a few others, including professors Ahmad Rami and Muhammad Abdul-Wahab [1 (p. 117)].